Fluorine-doped tin oxide catalyst for glycerol conversion to methanol in sub-critical water - Samad, Wan Zurina; Goto, Motonobu; Kanda, Hideki; W., Wahyudiono; Nordin, Norazzizi K.; Kin Hong, Liew; Yarmo, Mohd Ambar; Yusop, Muhammad Rahimi (Elsevier B.V., 2017)
In this study, a method for the catalytic conversion of glycerol to methanol in sub-critical water (subCW) is proposed. Glycerol conversion to methanol using the subCW method is a new attempt to the best of the authors's knowledge and this process was compared with the conventional hydrogenolysis method. For the first time, fluorine-doped tin oxide (FTO) was applied as a novel heterogeneous catalyst for the conversion of glycerol to methanol. The sub-critical reaction was conducted under optimal and mild conditions at a reaction temperature of 300 °C, reaction time of 30 min, and at a low pressure sufficient to maintain the liquid phase. Initial feedstock (glycerol) concentration and catalyst amount of 20 wt% and 0.01 g respectively, were utilized and glycerol conversion and methanol selectivity were measured using gas chromatography-flame ion detector (GC-FID) analysis. Optimum glycerol conversion of ∼80% was achieved, with methanol as the major product with a selectivity of ∼100%. The subCW method can also be applied for extraction processes as well as biomass conversion by optimizing some parameters such as reaction time, catalyst amount, reaction temperatures, and catalyst cyclability.